Legal Protection of Women and Children Victims of Sexual Violence in Gorontalo City Police - Nopiana Mozin; Lucyane Djaafar; Risha Safitri Ibrahimr (LEGAL BRIEF, 2023)
Legal protection in Indonesia is given to everyone based on equal rights and obligations as well as standing before the law. In this case, women and children are given extra legal protection because they are vulnerable to becoming victims of violence. In Gorontalo itself, the number of sexual violence increases every year. This is corroborated by the findings of cases of sexual violence from November 2019 to 2022, namely 105 cases. Regarding protection, the Gorontalo City Police Women's and Children's Service Unit has a role in protecting against all forms of violence, especially sexual violence. Sexual violence is defined as forced sex that can be performed by anyone who does not care about their relationship with the victim. The method used in this research is qualitative analysis, where research findings are obtained from literature research, document studies, and interviews. The purpose of this research is to find out legal protection efforts for women and children who are victims of sexual violence in Gorontalo and what are the inhibiting factors for legal protection for children and women who are victims of sexual violence themselves. In the findings of this study, legal protection for women and children who were victims of sexual violence, namely that victims immediately received assistance from the Integrated Service Center for Empowerment of women and children (P2TP2A) at the Gorontalo City Police in the initial process. Assistance is focused on the mental and psychological health of the victim. After that, if the victim is not satisfied with the process, the Integrated Women and Children Empowerment Service Center (P2TP2A) will assist the victim in submitting a report to the National Police so that it is followed up through the court process. The inhibiting factors found in this study were the victim's uncooperativeness in providing information due to mental disturbances due to trauma, as well as the location of the victim's house which was quite far away in terms of the process of providing legal protection itself.